Kapatid - Dineros, Beverly Anne (Animo Repository, 1990)
This is a video documentary on KAPATID (Kapisanang Para sa Pagpapalaya at Amnestiya ng mga Detenido sa Pilipinas). A non-government organization working for the release and amnesty of political detainees in the Philippines. This documentary intends to show how KAPATID provides assistance to political detainees and their families through a presentation of Sammy de Castro's case. It was shot on Video 8, transferred and edited in U-matic, with a running time of 27 minutes.